If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 6x = 6 + 3x Solving 3 + 6x = 6 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 3 + 6x + -3x = 6 + 3x + -3x Combine like terms: 6x + -3x = 3x 3 + 3x = 6 + 3x + -3x Combine like terms: 3x + -3x = 0 3 + 3x = 6 + 0 3 + 3x = 6 Add '-3' to each side of the equation. 3 + -3 + 3x = 6 + -3 Combine like terms: 3 + -3 = 0 0 + 3x = 6 + -3 3x = 6 + -3 Combine like terms: 6 + -3 = 3 3x = 3 Divide each side by '3'. x = 1 Simplifying x = 1
| 3x-2+2x+3x-2+2x= | | -0.17-(14.6)=g | | -3+4x=7-x | | 3(n-7)=2n-8 | | u^2+12u+36=0 | | 7+2x=-3+4x | | -3x+8=x-12 | | 2w^4x^4-32w^4= | | 2x+1/4+9/4 | | y=7x+37 | | 16u^2-u^2v^4= | | 2x-8(0)=24 | | 2(0)-8y=24 | | 0.2+6.51+2.03=a | | -8y=2 | | 3y=9x-24 | | -12.5+20.13=W | | x+x+0.56+x+0.56+1.08=10.51 | | c=9.8+(-2.5) | | 2x^2-3xy-5y^2=0 | | y=-12+(-9.6) | | y=1/4(0)-2 | | m/5+5=7/5 | | 2x-3xy-5y=0 | | y=1/4(4)-2 | | (11/12/44/5)-(11/12*44/5) | | 14.75+0.18=k | | 8-5x=4-6x | | 15/48=54 | | 8-1x=4-6x | | -6x^2+5y+6=0 | | 5y^2+34y+24=0 |